The role of nutritional medical therapy on nutritional status, functional capacity and quality of life of pulmonary tuberculosis patients with difficulty - Nugrahayu Widyawardani; Tjandraningrum -; Yohannessa Wulandari (World Nutrition Journal, 2022)
Pulmonary tuberculosis (pulmonary TB) is a chronic infectious disease with high levels of morbidity and mortality. Metabolic changes due to tuberculosis Mycobacterium infection and activation of the neurohormonal system contribute to the occurrence of malnutrition, which can have a negative effect on the prognosis of patients with pulmonary TB, as well as decreased functional capacity and quality of life. The provision of medical nutrition therapy from the beginning of diagnosis is upheld, supporting the recovery process of TB patients. In this series of cases, there were four cases of Pulmonary TB patients with difficulty, namely TB billion, chronic obstructive pulmonary disease (COPD), and meningitis TB. At the beginning of the examination, there was a deficiency of macronutrients and micronutrients, hypoalbuminemia, anemia, and decreased functional capacity and quality of life. Medical nutrition therapy is administered individually, according to clinical conditions such as TB with mild, moderate and severe malnutrition, those are gradually weight loss and muscle wasting when the symptoms start until treated in intensive care unit (ICU) and hospital ward. According to laboratory parameters such as anemia, hypoalbuminemia, and a history of food intake analysis such as hypocaloric and starvation.